2013
DOI: 10.5005/jp-journals-10024-1295
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Oral Mucosal Lesions in a Group of Iranian Dependent Elderly Complete Denture Wearers

Abstract: Aim: Oral mucosal lesions are frequently observed in institutionalized elderly patients more than other age groups. The aim of this study was to determine the prevalence of epulis fissuratum and denture stomatitis and their associated causes in dependent elderly complete denture wearers. Materials and methods:This study was conducted in dependent elderly complete denture's wearers living in four randomly selected nursing homes located in Tehran. Associated factors such as gender, age, use of medication, site o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
2
26

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(44 citation statements)
references
References 17 publications
(38 reference statements)
1
15
2
26
Order By: Relevance
“…Studies that did not mention dental status and the elderly were eliminated during the primary screening. Case reports and letters to the editor, studies on unhealthy populations (ie diabetics, patients with cardiovascular diseases, transplant patients, periodontal patients, and opioid users), studies on the correlation of tooth loss and risk of cancer, studies with incomplete information, studies on radiographic findings, and those with low mean age of patients were all excluded (Figure 1) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies that did not mention dental status and the elderly were eliminated during the primary screening. Case reports and letters to the editor, studies on unhealthy populations (ie diabetics, patients with cardiovascular diseases, transplant patients, periodontal patients, and opioid users), studies on the correlation of tooth loss and risk of cancer, studies with incomplete information, studies on radiographic findings, and those with low mean age of patients were all excluded (Figure 1) …”
Section: Resultsmentioning
confidence: 99%
“…Case reports and letters to the editor, studies on unhealthy populations (ie diabetics, patients with cardiovascular diseases, transplant patients, periodontal patients, and opioid users), studies on the correlation of tooth loss and risk of cancer, studies with incomplete information, studies on radiographic findings, and those with low mean age of patients were all excluded (Figure 1). [16][17][18][19][20][21][22] Findings regarding the dental status of elderly Iranians and retrieved studies on this topic are presented in Table 1. With regard to the sampling method, the majority of reviewed studies used random sampling for data collection, except for Aghili et al 23 Instead, they sampling for patients referred to a place.…”
Section: Re Sultsmentioning
confidence: 99%
“…The majority of the studies analyzed (16-24) report different rates of prevalence, all within this range. On the other hand (25-28), reported rates of prevalence of denture stomatitis lower than 6%.…”
Section: Discussionmentioning
confidence: 97%
“…Atashrazm et al (24) reported 31 cases of IPH in a group of 201 complete denture wearers. The authors mention the presence of vacuum suction in all maxillary dentures and suggest a possible relationship with IPH.…”
Section: Discussionmentioning
confidence: 99%
“…The oral cavity of elderly adults is prone to a wide number of oral pathologies, varying from nonneoplastic conditions to benign and malignant diseases . A rare case of oncocytic papillary cystoadenoma with crystalloids of the nontyrosine type in a elderly woman with an atypical presentation is presented.…”
mentioning
confidence: 98%